INCIDINCE OF STREPTOBA CILLUS MONILIFORMIS IN LABORATORYRATS AND MICE - l-Iadeel; AL- Hadithi (Basrah Journal of Veterinary Research)
Conjunctiva ofthirty rats and ten mice were examined for the presence ofthe normal ﬂora Streptobacillus moniliformis which is the causative agent of rat-bite fever in man . 60 % of each rats and mice were found to harbor. this bacteria suggesting a potential source for human infection . biochemical characterization revealed occurence of biotypes which are valuable in tracing epidemics . A test for pathogenicity was carried out on rabbite